2019
DOI: 10.1104/pp.18.01371
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Regulated HLP1 Acts as a Key Molecule in Governing Thermomemory

Abstract: Induction of heat shock proteins (HSPs) in response to heat stress (HS) is indispensable for conferring thermotolerance. Glc, a fundamental signaling and metabolic molecule, provides energy to stressed seedlings to combat stress. The recovery of stressed plants from detrimental HS in response to Glc is largely mediated by HSPs, but the mechanistic basis of this thermotolerance is not well defined. In this study, we show that Glc has a prominent role in providing thermotolerance. Glcmediated thermotolerance inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 78 publications
1
44
0
Order By: Relevance
“…In addition, we showed that different sets of genes, including FBA6, are involved in generating HS memory in the SAM and cotyledons. To date, only three of the 21 HSFs in Arabidopsis had been shown to participate in HS memory: HSFA1a, HSFA2, and HSFA1e (19,20,29,40). Here, we provide molecular evidence that eight HSFs are likely involved in thermomemory in the SAM.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, we showed that different sets of genes, including FBA6, are involved in generating HS memory in the SAM and cotyledons. To date, only three of the 21 HSFs in Arabidopsis had been shown to participate in HS memory: HSFA1a, HSFA2, and HSFA1e (19,20,29,40). Here, we provide molecular evidence that eight HSFs are likely involved in thermomemory in the SAM.…”
Section: Discussionmentioning
confidence: 66%
“…The glc-TOR-E2Fa signaling pathway has also been implicated in thermotolerance and thermomemory [ 157 , 158 ]. Glc-activated TOR phosphorylates E2Fa which binds to the promoter of HLP1 (Hikeshi Like Protein 1), an ortholog of human Hikeshi.…”
Section: Tor Signaling In Photosynthetic Organismsmentioning
confidence: 99%
“…Glc-activated TOR phosphorylates E2Fa which binds to the promoter of HLP1 (Hikeshi Like Protein 1), an ortholog of human Hikeshi. HLP1 binds to the promoters of many heat response genes and likely activates their expression and thus increases thermotolerance [ 157 ]. Additionally, TOR works in concert with p300 histone acetyltransferase 1 (HAC1) and HLP1 to modulate the chromatin acetylation of heat stress loci and impart short-term acquired thermotolerance.…”
Section: Tor Signaling In Photosynthetic Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…TOR phosphorylates E2Fa, which in turn binds to the promoters of target genes to drive their expression 10,40 . To identify the possible role of E2Fa in regulating the expression of FLZ8, we analyzed the presence of the E2Fa binding sites in the promoter region of FLZ8.…”
Section: Sugar Sufficiency and Tor Induce The Expression Of Flz8 By Hmentioning
confidence: 99%